Variability and Source Characterization of Regional PM of Two Urban Areas Dominated by Biomass Burning and Anthropogenic Emission - Christian Mark G. Salvador; Jhon Robin dR. Yee; Iara Chantrelle V. Coronel; Angel T. Bautista; Raymond J. Sugcang; Mark Anthony M. Lavapiez; Rey Y. Capangpangan; Preciosa Corazon B. Pabroa (Aerosol and Air Quality Research)
Abstract Identifying the sources and formation pathways of particulate matter (PM) and its components is important to determine the impact of atmospheric aerosols on human health and the warming of the global atmosphere. Here, we characterized the variability of the eleven-year concentration and the origin of PM2.5 in two urban regions (Metro Manila and Boracay) in the Philippines, a country in South East Asia (SEA) with high local anthropogenic emissions and frequently impacted by transboundary pollution. The surface concentration of PM2.5 was analyzed using simulated and reanalyzed satellite data (MERRAero), complemented, and validated with filter measurements for PM2.5 and black carbon (BC). The PM2.5 masses in Metro Manila (12.3 ± 2.4 µg m−3) and Boracay (12.9 ± 3.6 µg m−3) were comparable yet with varying concentrations of aerosol components Anthropogenic related components of PM (organic carbon, sulfate, and BC) were more enhanced in the metropolis region (4.9 µg m−3) than in the prime tourist spot (2.72 µg m−3). Sulfate formation impacted the aerosol mass in Metro Manila, with the photochemical oxidation of SO2 as the predominant production pathway of sulfates. Analysis of regional organic matter (OM) and BC in Boracay revealed extensive transboundary transport of biomass burning (BB) plumes from equatorial SEA countries. Also, the ratio of OM and SO4 was utilized as a quick proxy for source characterization. Metro Manila and Boracay reported 0.77 ± 0.20 and 1.06 ± 0.55, highlighting the evident impact of traffic emissions in the PM mass in the metropolis region. For Boracay, the mixed contributions of BB and vehicular activities influenced the formation of PM. Overall, the reanalysis of satellite data captured the long-term variability and origins of surface PM in two vital urban regions in the Philippines. The utilization of MERRAero will be an important procedure in making regulatory decisions on regional pollution control.